SEPOK: Komunitas Sepeda Ontel di Kota Pontianak Kalimantan Barat - Arkanudin Arkanudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Nowadays, there are various communities in all parts of Indonesia. Likewise, Pontianak City, known as the Equator City, also has an ontel bicycle community. In the era of globalization with the offer of modern lifestyles, this community chooses the classic mode of transportation. The aim of the study is to analyze the emergence of the ontel cycling community, its conservation activities and the importance of ontel bicycles in this community. Data were collected through observation, interviews, document studies and analyzed qualitatively. The results found that the community is very active in participating in ontel bicycle culture preservation activities at the local, national and international levels as well as in other fields. Members of the community are diverse and have different views on the meaning of the bicycle as a symbol.